FUNGSI DAN MAKNA PAWON PADA ARSITEKTUR SUNDA - Nuryanto, Nuryanto (TERAS)
Pawon or kitchen own the very important role in house, that is as cooking area. At colonial period in Indonesia, kitchen have been known as by the part of house. For power which start to recognize the assistant, hence kitchen building develop; builded by a backside separate from by especial house, or its space intentionally be placed by a backside from home, with the reason that kitchen assessed by as special space to cook and represent the ministrant domain.Â At traditional architecture of Sundanese Society, pawon or kitchen is also placed by a house backside. The difference with colonial period which its kitchen situation rear, because kitchen assessed by as ministrant domain, in traditional architecture of Sundanese Society, kitchen situation rear more relied on by its symbolic meaning consideration, that is as symbol of deadly and symbol of womanly. Pawon at traditional architecture of Sundanese Society own two function: Social function and Ritual function.Â As the conclusion, if seen from its function intensity, hence pawon represent the symbol of womanly (kawanitaan), because its activity is conducted by woman clan (wanita). But, if seen from its meaning intensity, hence pawon own the symbol of deadly, because sliverring its relation with the death.Â